Complications in pediatric interventional neuroradiology management. Reflections on a personal experience. Issue 6 (December 2020) - Rodesch, Georges; Smajda, Stanislas
Pediatric interventional neuroradiology is a rewarding but demanding specialty. It cannot be classified as a miniaturized technical procedure simply because it deals with small vessels in small patients but remains a field requiring specific knowledge combining clinical, anatomical, physiologic, and technical features. Complications that occur remain terrible experiences in this population whose patients have not personally requested to be treated for their vascular malformations. The aim of this article is to evoke the various possible groups of complications that may occur during a pediatric endovascular procedure in order to make physicians aware of these problems and help them to avoid them.